Amino-Terminal Precursor Sequence Modulates Canine Distemper Virus Fusion Protein Function - von Messling, Veronika (American Society for Microbiology, 2002)
The fusion (F) proteins of most paramyxoviruses are classical type I glycoproteins with a short hydrophobic leader sequence closely following the translation initiation codon. The predicted reading frame of the canine distemper virus (CDV) F protein is more complex, with a short hydrophobic sequence beginning 115 codons downstream of the first AUG. To verify if the sequence between the first AUG and the hydrophobic region is translated, we produced a specific antiserum that indeed detected a short-lived F protein precursor that we named PreF(0). A peptide resulting from PreF(0) cleavage was identified and named Pre, and its half-life was measured to be about 30 min. PreF(0) cleavage was completed before proteolytic activation of F(0) into its F(1) and F(2) subunits by furin. To test the hypothesis that the Pre peptide may influence protein activity, we compared the function of F proteins synthesized with that peptide to that of F proteins synthesized with a shorter amino-terminal signal sequence. F proteins synthesized with the Pre peptide were more stable and less active. Thus, the Pre peptide modulates the function of the CDV F protein. Interestingly, a distinct two-hit activation process has been recently described for human respiratory syncytial virus, another paramyxovirus.